The Extent of Principals’ Empowerment and Their Functions towards Management of Public Elementary Schools - PAULA ANJELICA P. RIVERA; FLORANTE P. IBARRA (Indonesian Research Journal in Education |IRJE|, 2020)
This study examined the relationship between the extent of empowerment of public elementary school principals and their functions towards school management in the District of Aliaga, Nueva Ecija, Philippines. 18 public elementary principals/school heads were involved. Anchored on Zimmerman’s (2000) empowerment theory, both process and outcomes-based empowerment had been carefully assessed. This lens provided principles and framework in looking at processes such as individual action and engagement activities within a particular social context. Survey questionnaire was used involving statements measured through Likert scale. With a six-month period of data gathering, Pearson r was utilized in the analysis. Results revealed that instructional (r=.408, p <0.01) and administrative empowerments (r=.776, p <0.01) established highly significant relationships with school safety and orderliness, opportunities to learn, time on task and instructional leadership respectively. Recommendations on sustainability of quality instruction in relation to school-based management are further taken into account as these might likewise impact the teaching and learning process to enhancing the identity of instructional leadership.